Politics in concrete: social production of space in Diyarbakır, 1999-2014 - Genç, Fırat. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2014., 2014)
This study examines the processes of production of space in Diyarbakır in the period 1999-2014 so as to explore the conditions under which neoliberal urbanism, as a certain mode of politics of space, becomes hegemonic. Analyzing the material, institutional and ideological dimensions of both the urban regeneration process in the historic city center and the suburbanization and residential differentiation in the outskirts, it reveals the ways in which hegemony of urban neoliberalization is politically constructed, the grounds on which this construction is based upon, and the interaction of imaginations, values and desires that shape these grounds. Focusing on the struggles to reconfigure the city’s physical, historic and cultural landscapes, it elucidates the encounters between the “post-war” hegemony project of the historical bloc represented by the AKP and the Kurdish political movement’s “post-colonial” counter-hegemony project. Recent political-economic dynamics that have reconfigured physical and social spaces of major cities in Turkey are often pictured as fixed policy packages which are disseminated from top to bottom and from center to periphery, put forward by the initiative of homogenous elites. Deployment of the notion of neoliberalism in such economistic and state-centric manner underestimates the hegemonic character of neoliberal urbanism. Against this conventional understanding of contemporary urban processes, this dissertation demonstrates that neoliberal urbanism is a conflictual, politically-constructed, twofold process of commodification and depoliticization which intrinsically contains moments of destruction and creation.
Keywords: City planning -- Turkey -- Diyarbakır.; Urbanization -- Turkey -- Diyarbakır.